Formation of Industrially Important Chemicals from Thermal and Microwave Assisted Oxidative Degradation of Industrial Waste Lignin - Nagpurkar, L.P.; Chaudhari, A.R.; Ekhe, J.D. (Asian Journal of Chemistry, 2010)
The lignin recovered from the industrial waste black liquor which was obtained from Simplex Paper Mills, Gondia, Maharashtra State, was subjected to purification using 1,4-dioxane. The purified lignin was oxidized using alkaline nitrobenzene as an oxidizing agent by the thermal degradation method and under the microwave irradiation. The low molecular weight compounds formed during the degradation were extracted and analyzed through HPLC. p-Hydroxybenzaldehyde and vanillin were the main compounds identified. Formation of some other compounds was also noticed. These studies have established the merits of microwave technique over conventional thermal degradation of lignin oxidation at normal pressure. It also provides the simpler method for the determination of above two important chemicals for systematic study and also explores the possibilities of utilization of industrial waste–alkali lignin.